Impact of selexipag use within 12 months of pulmonary arterial hypertension diagnosis on hospitalizations and medical costs: A retrospective cohort study - Yuen Tsang; Michael Stokes; Yong‐Jin Kim; Rong Tilney; Sumeet Panjabi (The Clinical Respiratory Journal, 2023)
Abstract Background Oral selexipag, a prostacyclin pathway agent (PPA), is effective in patients with pulmonary arterial hypertension (PAH). The objective of this study is to assess the impact of initiating oral selexipag within 12 months of diagnosis on health outcomes. Methods This retrospective cohort study used data from Optum's de‐identified Clinformatics® Data Mart Database. PAH patients between 1 October 2015 and 30 September 2019 were included. Patients were also required to have received PAH medication within 12 months of their initial diagnosis. Study groups included patients who initiated selexipag within 12 months of PAH diagnosis (SEL ≤ 12) and those who did not initiate any PPA within 12 months of PAH diagnosis (No PPA ≤ 12). Inverse probability of treatment weighting was used to remove potential confounding between groups. Cox and Poisson regression models were used to compare hospitalization and disease progression. Generalized linear model with gamma distribution and log link was used to compare costs. Results SEL ≤ 12 had lower rate of all‐cause hospitalizations (rate ratio: 0.76, 95% confidence interval [CI]: 0.60, 0.96) versus no PPA ≤ 12, but no differences in PAH‐related hospitalization rate (rate ratio: 1.03, 95% CI: 0.79, 1.33) or risk of disease progression (hazard ratio: 1.01, 95% CI: 0.71, 1.44). SEL ≤ 12 incurred lower all‐cause (mean difference: −$23 623; 95% CI: −35 537, −8512) and PAH‐related total medical costs (mean difference: −$12 927; 95% CI: −19 559, −5679) versus no PPA ≤ 12. Conclusion Selexipag initiation within 12 months of PAH diagnosis demonstrated reductions in all‐cause hospitalization rate and medical costs.